Smart fan - Adam, Muhammad Hafidz; Amlan, Mohd Shafiq (2016)
It is typical to said that when we feel so hot under the sunny days we will find a fan to cool down our body temperature by getting wind that came from the windows or if we had air conditioning at home we switch on the air conditioning at the low temperature to make get our body temperature comfortable with the temperature surroundings. We also will find a fan that can blows their wind only just in one direction and not rotating when we get near to the fan So when the person get near to the fan, the sensor that we stick to the fan will detecting the person and will make the fan stop from rotating and just blows the winds into one direction. So when the person goes away from the fan make their own ways to other places the fan will continue rotating until the sensor detecting the person. The fan also have temperature sensor that can increase the speed of the fan when the temperature surrounding getting hotter ( above than 25C) . If the temperature of the days below than 25C the speed of the fan will remains same and not rise up the speed. Both of the systems were simulated in Proteus 8.0 software which is simulating the circuit if it can produce the output that desired. The design of the circuit which is Printed Circuit Board (PCB) also designed in the Proteus 8.0 .